Everyday Americans - Canby, Henry Seidel, 1878-1961 (Salt Lake City, UT : Project Gutenberg, 2020)
"Everyday Americans" by Henry Seidel Canby is a reflective essay written in the early 20th century. This work provides an exploration of the American mind, particularly in the context of the effects of World War I on American identity and values. The author seeks to depict the traits of the typical American, particularly those of the old stock and recent graduates, while emphasizing how the war has influenced their sense of nationality and believed ideals. The opening of the text positions itself firmly away from being a war book, although it is framed as a response to the war's aftermath, inviting readers to consider how the experiences of conflict have shaped perceptions of the American character. Canby's preface reveals his fascination with the "conservative-liberal" type prevalent in America, suggesting a complex relationship between traditional values and modern political thought. He seeks to analyze the nuances of American political behavior, particularly among the college-educated class, and sets up a framework for subsequent chapters that will delve into various dimensions of American society, its ideals, and challenges. (This is an automatically generated summary.)
The American mind -- Conservative America -- Radical America -- American idealism -- Religion in America -- Literature in America -- The bourgeois American.
Release date is 2020-08-31
E-text prepared by David E. Brown and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: National characteristics, American